Case managers within general practices in 11 Western countries: repeat cross-sectional studies (Swiss Medical Weekly, 2024)
BACKGROUND: In the context of an ageing population and increasing health needs, primary care reform is needed and several new models have emerged, including the introduction of case managers in general practitioner practices.AIM: To describe the frequency of case managers in general practices in eleven Western countries between 2012 and 2019 and to investigate the characteristics of general practitioners and their practices associated with case manager frequency.METHODS: A secondary analysis of the Commonwealth Fund International Health Policy Surveys of Primary Care Physicians, which were international cross-sectional studies conducted in 2012, 2015 and 2019. Random samples of general practitioners were selected in 11 Western countries (2012: n = 9776; 2015: n = 12,049; 2019: n = 13,200). The use of case managers in general practitioner practices was determined with the question “Does your practice use personnel, such as nurses or case managers, to monitor and manage care for patients with chronic conditions that need regular follow-up care?”, with possible answers “Yes, within the practice”, “Yes, outside the practice”, “Yes, both within and outside the practice” or “No”. Other variables characterising general practitioners and their practices were considered. Mixed-effects logistic regression was performed.RESULTS: The frequency of case managers within general practitioner practices varied greatly by country, with an overall trend towards an increase from 2012 to 2019. In the multivariate analysis, more case managers were found in practices located in small towns (odds ratio [OR] 1.4; 95% confidence interval [CI] 1.2–1.7) and in rural areas (OR 1.9; 95% CI 1.5–2.4) compared to cities. The frequency of case managers was higher in larger practices, as shown in comparisons of practices in the second, third and fourth quartile of full-time equivalent employee counts compared to those in the first quartile (Q2: OR 1.7, 95% CI 1.4–1.9; Q3: OR 2.1, 95% CI 1.6–2.9; Q4: OR 3.8, 95% CI 3.0–4.9). There was no significant difference in frequency with respect to the age and sex of the general practitioners.CONCLUSION: The use of case managers in general practitioner practices is a promising approach, but its practice varies greatly. This practice has been developing in Western countries and is tending to increase. The implementation of case managers seems to be associated with certain characteristics linked to general practitioner practices (practice location, practice size), whereas it does not seem to depend on the personal characteristics of general practitioners, such as age or sex.